Twenty miles per hour speed limits: a sustainable solution to public health problems in Wales. Issue 7 (23rd March 2017) - Jones, Sarah J; Brunt, Huw
Abstract : Background: Prevention, rather than treatment, is the key to longer healthier lives. Identifying interventions that will impact positively on road traffic injuries, air quality and encourage active travel is a significant public health challenge. This paper aimed to explore whether 20 mph limits could be useful in achieving this. Methods: Research evidence was reviewed to identify the effect of 20 mph zones and limits on health and well-being. The evidence was then used to estimate the effect of a change to a 20 mph limit on road traffic casualties and air pollution. It was then mapped against the seven goals of the Well-being of Future Generations Act (2015). Results: If all current 30 mph limit roads in Wales became 20 mph limits, it is estimated that 6–10 lives would be saved and 1200–2000 casualties avoided each year, at a value of prevention of £58M–£94M. In terms of air pollution, deaths attributed to nitrogen dioxide (NO2 ) may increase by 63, and years of life lost by 753. However, deaths attributed to particulates (PM2.5 ) may decrease by 117 and years of life lost by 1400. Evidence review suggests benefits in terms of road traffic casualties, air quality, active travel, noise pollution, greater social inclusion, greater community cohesion and local business viability. Conclusions: Road traffic injuries, air pollution and obesity are an inter-related, interdependent triad. The challenge facing public health today is identifying robust interventions that will have positive effects on all three as a minimum; default 20 mph limits is the solution to increasing public health problems in Wales.